Karbonisasi Pelepah Sawit Dengan Variasi Temperatur Dan Waktu Karbonisasi - Sitorus, Mesakh Fridolin; Komalasari, Komalasari; Helwani, Zuchra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Palm fronds only used as a source of raw materials for animal feed, compost and organic fertilizer in the garden area so far. The heating value of palm fronds is 15,184 MJ/kg. The heating value can be improved by conducting carbonization process. Carbonization is a method to process biomass into solid fuel without oxygen where the temperature range is between 400-600 Â°C.The aim of this study is to produce a solid fuel from palm fronds by using carbonization process and studied the effect of variations in temperature (450-550 Â°C) and carbonization time (3-4 hours) on the quality of fuels from waste palm frond.Carbonization temperature used were 450, 500, 550oC, carbonization time used were 3, 3.5, 4hours. Particle size used were < 850 Î¼m (20 mesh).The highest result of heating value was 27,177MJ/kg at 450oC for 3.5hours. The lowest result of volatile matter content was 7,01 %-wt at 550oC for 3hours. Significant process condition affecting the heating value was temperature and carbonization time.Keywords : Carbonization, Heating Value, Palm Frond, Volatile Matter